Design modification in overdentures with precision attachments in a case of reduced vertical dimension - Anuj Wangoo; Sakshi Malhotra; Ramanpreet Singh; Yashendra (Wolters Kluwer Medknow Publications, 2015)
Overdentures is a preferred treatment option in patients who have to go for extraction of the remaining teeth for fabrication of complete dentures. The teeth which are preserved, play a vital role by improvement of crown root ratio, provide proprioception, decrease the rate of resorption, and improve support to the denture. Rehabilitation using overdentures is a widely accepted preventive approach due to its ease of fabrication and the successful prognosis. An over denture is a preventive prosthodontic concept with a multidisciplinary approach involving periodontic, endodontic, and prosthodontic intervention. An overdenture improves retention, stability, maintains proprioception, prevents residual ridge resorption, and improves patient satisfaction. This is a case report of a patient with few remaining teeth, successfully treated with Preci-Sagix (Ceka attachments Preci-line, Belgium) overdenture attachments.